Development of a wearable resonator mask for breathing rate monitoring - Yusnita Rahayu; Tasya Kirana; Jack Ping Soh (JURNAL INFOTEL, 2023)
As one of the processes of patient care, diagnosis, and monitoring are the most important steps in the medical field. Sleep apnea is a problem that affects about 25 million Americans, and 80% of them go untreated because it is not identified. Monitoring has a big role in making patient treatment decisions. So this research aims to produce a wearable resonator mask that can work as a breathing rate monitor. The proposed resonator will use the relative humidity generated during the respiration process. The resonator uses a textile jeans material that is flexible, comfortable, and fits on a mask. Testing is carried out in 3 different positions; lying down, sitting, and standing. There is a difference in the percentage of RH produced from each position based on the difference in the frequency range produced. The proposed resonator operates well at 3.9 GHz.